Hollywood or history? : an inquiry-based strategy for using film to teach about inequality and inequity throughout history - Kaka, Sarah (Emerald Publishing Limited : Information Age Publishing, Inc., 2022)
"The rationale for the present text, Hollywood or History? An Inquiry-Based Strategy for Using Film to Teach About Inequality and Inequity Throughout History stems from two main things. First and foremost is the fact that the reviews of the first two volumes in the Hollywood or History? series have been overwhelmingly positive, especially as it pertains to the application of the strategy for practitioners. Classroom utility and teacher practice have continued to be the primary objectives in developing the Hollywood or History? strategy. The second thing is that this most recent volume in the series takes it in a new direction--rather than focusing on eras in history, it focuses on the themes of inequity and inequality throughout history, and how teachers can utilize the Hollywood or History? strategy to tackle some of the more complicated content throughout history that many teachers tend to shy away from. There is a firm belief that students' connection to film, along with teachers' ability to use film in an effective manner, will help alleviate some of the challenges of teaching challenging topics such as inequity and inequality in terms of gender, race, socioeconomic status, and so much more. The book provides 30 secondary lesson plans (grades 6-12) that address nine different topics centered around inequity and inequality throughout history, many of which connect students to the world we are living in today. The intended audience for the book are teachers who teach social studies at the 6th-12th grade level both in the United States and other countries. An additional audience will be college and university social studies/history methods professors in the United States and worldwide"-- Provided by publisher.
Keywords: Equality -- Study and teaching -- United States.; Social history -- Study and teaching -- United States -- Audio-visual aids.; Historical films -- United States -- History and criticism.; Motion pictures in education -- United States.; Education -- Teaching -- Subjects -- Social Science.; Teachers classroom resources and material.; Teaching of a specific subject.; Educational: Social sciences, social studies.; elektronické knihy; electronic books